Myśl polityczna i struktury organizacyjne ruchu anarchistycznego w państwach Unii Europejskiej w dobie przemian globalizacyjnych - Malendowicz, Paweł (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The subject of this study is the transformation of the organizational structures, as well as in the political thought in the Western European anarchist movement during the period of rapid globalization. The research period runs from 1991-2010. Material for the research was provided by printed matter as well as Internet news and articles, documents and the author’s correspondence with the representatives of the European anarchist movement. The main method/technique of the survey involved the analysis of source texts. The author also employed his own research experience and observations of anarchism. Contemporary globalization processes are characterized by contradictory directions of development. They are expressed in the unification of the terrorist movement on one hand, and the diversification of its forms on the other. The goals of the anarchist movement and its main trends of thought are changing and dispersing. The achievement of full freedom, however, remains the primary goal of anarchists, while all other goals are secondary.
The anarchist movement’s political thought and organizational structures in European Union states at the time of globalization transformations